2020
DOI: 10.3390/en13051284
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Pyrolysis of Municipal Plastic Waste Using Me/Ni/ZSM-5 Catalysts: The Effect of Metal/Nickel Ratio

Abstract: This work is dedicated to the high temperature pyrolysis of municipal plastic waste using Me/Ni/ZSM-5 catalysts. Catalysts were synthetized by wet impregnation. In addition to nickel, synthetic zeolite catalysts contain calcium, ceria, lanthanum, magnesia or manganese. Catalysts were prepared and tested using 0.1, 0.5 and 2.0 Me/Ni ratios. Catalyst morphology was investigated by SEM and surface analysis. Higher concentrations of second metals can block catalyst pore channels due to the more coke formation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The procedure for the preparation of bimetalloaded catalysts and their main properties are summarised in earlier publication. 49 The Ni ). 49 The main properties of the Me/Ni/ZSM-5 catalysts are summarised in Table 3.…”
Section: Catalystsmentioning
confidence: 99%
See 4 more Smart Citations
“…The procedure for the preparation of bimetalloaded catalysts and their main properties are summarised in earlier publication. 49 The Ni ). 49 The main properties of the Me/Ni/ZSM-5 catalysts are summarised in Table 3.…”
Section: Catalystsmentioning
confidence: 99%
“…In our earlier studies, significant effect of these catalysts on the waste polymer pyrolysis has been reported. 48,49 At first, the synthetic ZSM-5 catalyst supporter had been impregnated by nickel, then the Ni/ZSM-5 catalyst was further loaded by different elements (Ca, Ce, La, Mg, Mn). The procedure for the preparation of bimetalloaded catalysts and their main properties are summarised in earlier publication.…”
Section: Catalystsmentioning
confidence: 99%
See 3 more Smart Citations